Jurnal Proses Pra Produksi Ebook Cermat Bertani Dengan Kalender Tanam - Husnu Tazkiya Ulwah, Yuni Nur Rohmatilah, Amata Fami (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
The development of all-digital information technology facilitates access to e-book. The existence of e-books will certainly make it easier for readers to access the desired reading sources wherever and whenever. Therefore, we need an e-book design that is made as attractive as possible. E-book creation is carried out through several processes with graphic design concepts as a reference, namely pre-production, production and post-production. The method used in making this journal is an applied method, where this method aims to solve practical life problems. This journal aims to educate public about the pre-production process in making e-books. The pre-production process for making e-books includes design concepts, media, visualization, client briefs and brainstorming. The pre-production process is the key to producing an interesting e-book. This e-book which contains 41 pages aims to convey information in the form of an invitation to the public to be careful in farming using the planting calendar as an effort to minimize the occurrence of crop failure which is packaged in an attractive design and makes it easier for readers. The community is expected to be able to produce e-book works well, after getting to know the pre-production stage to continue at the production and post-production stages.